Lattice Constants, Structure, and Crystal Size of Nanocomposites LiOH/Activated Carbon and Rough Bamboo with Mass Variation - Yulia Febrina; Darvina, Yenni (Department of Physics, Universitas Negeri Padang, 2024)
Energy development is needed in everyday life, one of which is electrical energy. Batteries are reliable electrical energy in the operation of portable electronic devices. Batteries that are often used are lithium batteries. Lithium batteries have the ability to charge quickly, last long and have high energy power. The reality is that batteries often overheat, affecting the work of the battery. Efforts to improve the performance of lithium batteries are to improve the quality of the anode material. This study aims to determine the lattice constant, structure, and crystal size of carbon, activated carbon, LiOH and variations of LiOH nanocomposite/ rough bamboo activated carbon. This research uses the sol gel method and is characterized using XRD. The mass variations used are 40%: 60%, 50% : 50%, 60% :40%. Carbon has a cubic crystal structure, crystal size of 103 nm. Peak addition occurs on activated carbon because it undergoes an activation process. Activated carbon has a hexagonal crystal structure, smaller crystal size than carbon which 25 nm - 62 nm. LiOH has a tetragonal crystal structure, crystal size 81 nm - 108 nm. The LiOH phase generally has a tetragonal crystal structure, and the carbon phase has a rhombohedral crystal structure. In the 40%: 60% variation has the smallest crystal size of 23 nm - 42 nm, because the addition of activated carbon is more than LiOH so that it affects the crystal size. If the addition of activated carbon is more than LiOH, the crystal size will be smaller.